Physical and mechanical properties of oil palm lumber / Muhammad Azizul Radhi - Radhi, Muhammad Azizul (2012)
This study determines physical and mechanical properties of Oil palm trunk with variables of layer (S1, S2 and S3) and portion (top, Middle, Bottom) of that tree. The oil palm is selected to know whether this species is for various uses. The physical properties test is to determine the density and moisture content that was conducted in accordance to TAPPI standard T 258 OM- 94 (1996). The mechanical properties test is apply bending and compression tests. The test was conducted in accordance to the standard testing method, i.e. Britiish Standard (BS 373: 1957 Testing Small Clear Specimen of Timber). From the testing, Modulus of Elasticity (MOE), the Modulus of Rupture (MOR), Density and Compression of oil palm lumber are discovered.